Systematic Literature Review : Pengaruh Gaya Kepemimpinan Transformasional Dengan Kejadian Burnout Pada Perawat - Selvia, Dina; Hasipa, Hani Siti; Anjani, Sri Ulan; Nurizkiah, Riva; Depyanti, Sari Oktavia; Ridwan, Heri; Sutresna, Iyos (Jurnal Ilmiah Wahana Pendidikan, 2025)
Burnout is a syndrome that is experienced by many health professionals, including nurses who work in high-pressure conditions. In Indonesia, the prevalence of burnout in nurses reached 27.7% and in Jakarta it was 27.3%. One of the factors that causes burnout is the lack of organizational support, especially from superiors. Effective leadership styles are needed to address this problem, one of which is transformational leadership styles. This style plays an important role in improving the motivation, emotional well-being, and performance of nurses. This study aims to evaluate the relationship between transformational leadership style and the incidence of burnout in nurses to understand whether leadership style can significantly reduce burnout in nurses. This study used the Systematic Literature Review (SLR) method with the PRISMA method to identify relevant studies related to the relationship between transformational leadership style and burnout in nurses. Of the 556 articles that have passed the selection stage, 5 articles are ready to be synthesized. After the analysis, the findings from five studies showed that transformational leadership styles had an impact on nurse fatigue levels. It has been shown that transformational leadership styles affect nurses' burnout levels, which in turn can increase their motivation to deliver health services.